Orthopaedic Trauma Care Specialist Program for Developing Countries. (October 2015) - Slobogean, Gerard; Sprague, Sheila; Furey, Andrew; Pollak, Andrew
Abstract : Summary: The dire challenges faced in Haiti, both preearthquake and postearthquake, highlight the need for developing surgical infrastructure to care for traumatic musculoskeletal injuries. The proposed Orthopaedic Trauma Care Specialist (OTCS) residency program aims to close the critical human resource gap that limits the appropriate care of musculoskeletal trauma in Haiti. The OTCS program is a proposal for a 2-year residency program that will focus primarily on the management of orthopaedic trauma. The proposed program will be a comprehensive approach for implementing affordable and sustainable strategies to improve orthopaedic trauma care. Its curriculum will be tailored to the injuries seen in Haiti, and the treatments that can be delivered within their health care system. Its long-term sustainability will be based on a "train-the-trainers" approach for developing local faculty to continue the program. This proposal outlines the OTCS framework specifically for Haiti; however, this concept is likely applicable to other low- and middle-income environments in a similar need for improved trauma and fracture care.